Discovery of anatomic variant of saphenous nerve from human cadaver dissection - Ahmad, U.; San, Aye Aye; Cheah, Pike See; Mat Taib, Che Norma; Mohd Moklas, Mohamad Aris; Othman, Fauziah (Sociedade Brasileira de Anatomia, 2016)
Introduction: Saphenous nerve is the longest and largest pure sensory nerve, supplying the medial side of the thigh, leg and foot. Materials and Methods: In the present case study, during routine cadaveric dissection of the antero-medial part of the thigh, an interesting anomalous pattern of saphenous nerve was seen in the right lower limb of a 62 years old embalmed male cadaver from the Department of Human Anatomy, Universiti Putra Malaysia (UPM). Results: This saphenous nerve can be recognised as an unusual anatomical variant in which it gives a motor branch to the sartorius muscle during traversing the adductor canal and it was accompanied by blood vessels at the same time. The nerve continues its usual course and pierces the fascia lata, between the tendon of sartorius and gracilis and becomes subcutaneous. Conclusion: Knowledge of the variant anatomy of the saphenous nerve is important to surgeon in avoiding nerve injuries during adductor canal nerve block, nerve entrapment surgery, reconstructive surgery, pain management services and knee surgery successfully.